Prenatal Diagnosis and Management of Congenital Abnormalities of Central Nervous System - Bayar, Ülkü; Başaran, Mustafa; Usal, Deniz; Özcan, Oya; Kalaycı, Murat (Gynecology Obstetrics & Reproductive Medicine, 2006)
Among the congenital anomalies, central nervous system malformations are the most commonly seen ones whose antenatal sonographic diagnosis is very important. Sixteen cases, attempted to Karaelmas University Obstetrics Clinic, diagnosed as having central nervous system anomaly were presented. Ultrasonographic screening is a noninvasive method that should be recommended to all pregnant women. Second trimester ultrasonography is generally performed between 20-22 gestational weeks in order to detect fetal structural defects. In the early antenatal period the ultrasonographic diagnosis of major and minor anomalies will provide the chance of giving genetic counseling to families.